Crystallizing Religious Character in Early Childhood: An Analysis of the Teacher's Method at RA Almuslimun - Ali Iskandar Zulkarnain; Ajahari Ajahari; Abdul Azis; Saudah Saudah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study describes the method of crystallization of religious characters regarding faith, worship, and morals in children at RA Almuslimun Palangka Raya. This research was compiled using a descriptive qualitative approach, while the research subjects were 5 RA teachers. Data collection techniques used observation, interviews, and documentation, while data analysis used data collection, reduction, data presentation and making conclusions. Faith results of this study indicate that the crystallization of religious characters about faith uses the method of habituation, singing and stories. Meanwhile, regarding worship using habituation, demonstration, and memorization methods, while regarding morals/morals using habituation, advice, and example methods.